Thermal management and performance improvement by using coupled effects of magnetic field and phase change material for hybrid nanoliquid convection through a 3D vented cylindrical cavity - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
In this study, effects of using magnetic field and packed bed phase change material (PCM) system in a 3D cavity having ventilation ports on the performance improvements are analyzed during hybrid nanoliquid convection. Two different locations of inlet port is considered while the numerical study is conduced for various values (Reynolds number (Re, between 250 and 750), Hartmann number (Ha, between 0 and 100), size of the inlet (wd, between 0.15H and 0.85H) and nanoparticle loading amount (between 0.02 % and 0.1 % ). When PCM is used in the vented cavity, 13 % and 16.5 % enhancements of average Nusselt (Nu) number are obtained as compared to no-PCM case at Ha = 0 and Ha = 100. A critical Ha is obtained beyond which the phase transition time (tc) is reduced and the value depends upon the inlet port location. The location of the inlet port has significant impacts on phase change dynamics and transition time. When it is closer to the wall (case-C2), tc is reduced. 65 % and 80 % of reductions in the tc are observed at the highest Re for configurations C1 and C2. The higher port size resulted in fast phase transition while reduction of 89 % in tc is obtained at Re = 750 for case C1. Nanoparticle loading accelerates the phase transition and tc is reduced by 10.4 % and 9 % for cases C1 and C2. However, the average Nu variation with PCM shows different behavior for cases C1 and C2. At the highest particle loading, 11 % ( t = 52 min) and 13 % ( t = 250 min) increments in the average Nu are achieved C1 and C2. A polynomial type correlation for tc is obtained in terms of Ha and nanoparticle amount in the heat transfer fluid. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Vented cavity; Magnetic field; Phase change process; CFD; Nanoparticle loading